Double jeopardy: How lower levels of support during COVID-19 exacerbated the relationship between loneliness and distress - Bentley, Sarah V.; Young, Tarli; Álvarez, Belén; Jetten, Jolanda; Haslam, Catherine; Cruwys, Tegan; Casara, Bruno Gabriel Salvador; Crimston, Charlie R.; Dare, Michael; Ionescu, Octavia; Krug, Henning; Selvanathan, Hema Preya; et al. (Frontiers in Public Health, 2022)
While the relationship between loneliness and psychological distress is well documented, the mechanisms underlying this relationship are less clear. One factor known to be related to loneliness as well as psychological distress, is social support, with some studies suggesting that support–both received and provided–can serve as a mechanism to reduce the distress associated with loneliness. In this paper we examine the mediating role of both aspects of support in the relationship between loneliness and psychological distress in the COVID-19 context. We used a multi-country dataset collected at two timepoints during the pandemic; the first during the early stages (N = 6,842, 11 countries) and the second collected for a subset of countries (N = 1,299, 3 countries) 3 months later. Across all eleven countries, results revealed significant positive associations between loneliness and distress. Furthermore, using longitudinal data, we investigated the directionality of this relationship and found that increased loneliness over time was associated with increased psychological distress. The data also showed that both feeling unsupported and feeling unable to provide support to others mediated this relationship. These findings point to the need to facilitate people's ability to draw effective social support and help others–particularly at times when social connectedness is threatened–as a way of alleviating the psychological distress that commonly presents with loneliness.